2015
DOI: 10.1016/j.bbrc.2015.04.106
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic over-expression of YY1 induces pathologic cardiac hypertrophy in a sex-specific manner

Abstract: YY1 can activate or repress transcription of various genes. In cardiac myocytes in culture YY1 has been shown to regulate expression of several genes involved in myocyte pathology. YY1 can also acutely protect the heart against detrimental changes in gene expression. In this study we show that cardiac over-expression of YY1 induces pathologic cardiac hypertrophy in male mice, measured by changes in gene expression and lower ejection fraction/fractional shortening. In contrast, female animals are protected agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…A unique function of homodimeric ARNT as compared with heterodimeric ARNT is supported by recent studies that established the palindromic E-box motif CACGTG as a critical binding site for ARNT homodimers, while family, which is predominantly known to heterodimerize with other PAS family members to form heterodimeric transcription factors, classically with an α subunit of HIF or the dioxin receptor AHR to mediate hypoxia or xenobiotic responses by targeting correlation between ARNT and FKBP12/YY1 in multiple organ systems, including renal, cardiovascular, and digestive tissues, confirming our findings (GEO GSE3526, Supplemental Table 8) (48). In this context, previous reports implicate activation of a YY1 signaling axis as detectable in renal, cardiac, hepatic, and pulmonary pathologies and show that YY1 depletion protects from chronic organ failure (49)(50)(51).…”
Section: Discussionsupporting
confidence: 88%
“…A unique function of homodimeric ARNT as compared with heterodimeric ARNT is supported by recent studies that established the palindromic E-box motif CACGTG as a critical binding site for ARNT homodimers, while family, which is predominantly known to heterodimerize with other PAS family members to form heterodimeric transcription factors, classically with an α subunit of HIF or the dioxin receptor AHR to mediate hypoxia or xenobiotic responses by targeting correlation between ARNT and FKBP12/YY1 in multiple organ systems, including renal, cardiovascular, and digestive tissues, confirming our findings (GEO GSE3526, Supplemental Table 8) (48). In this context, previous reports implicate activation of a YY1 signaling axis as detectable in renal, cardiac, hepatic, and pulmonary pathologies and show that YY1 depletion protects from chronic organ failure (49)(50)(51).…”
Section: Discussionsupporting
confidence: 88%
“…YY1 is a transcriptional factor and plays a pivotal role in early heart development [35]. Its expression was elevated in the human failing heart, and caused pathologic hypertrophy [36]. The role of YY1 in ischemia is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…HF with preserved ejection fraction is also more common in women . Studies in rodent models demonstrate that when exposed to a predisposing factor or stimulus, females develop less hypertrophy than their male cohorts, even when exposed to identical levels of pathologic insult such as angiotensin II or transaortic constriction …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Studies in rodent models demonstrate that when exposed to a predisposing factor or stimulus, females develop less hypertrophy than their male cohorts, even when exposed to identical levels of pathologic insult such as angiotensin II or transaortic constriction. [6][7][8][9][10] Despite evidence that sex-based differences exist between men and premenopausal women in HF and other forms of heart disease, 1 large randomized clinical trials have not demonstrated a beneficial effect by treating postmenopausal women with hormone replacement therapy, 11 although a recent update of the Women's Health Initiative examined age dependence and concluded that there were some beneficial effects of estrogen in younger women. 12 Taken together, these findings underscore the need for a better understanding of the mechanisms responsible for the male-female difference in HF.…”
mentioning
confidence: 99%